Diagnostic performance of angiography-derived index of microvascular resistance: a systematic review and pooled meta-analysis. (3rd October 2022) - Zhou, J; Onuma, Y; Kotoku, N; Kageyama, S; Ninomiya, K; Masuda, S; Yan, H; Serruys, P
Abstract: Background: The index of microvascular resistance (IMR) is an established measurement of coronary microcirculation status. However, it has not been widely incorporated into routine practice due to need for intracoronary instrumentation (pressure wire) and hyperaemic agents. Several angiography-derived quantitative flow ratio-based indexes of microvascular resistance (angio-IMR) have been proposed rekindling the interest for the assessment and management of microvascular disease. Purpose: To review the overall diagnostic accuracy of angio-IMR against wire based IMR. Methods: A systematic review of the literature was performed and studies comparing angio-IMR with wire based IMR were included. Individual data was extracted using semi-automatic digitalization. Correlation of angio-IMR with IMR and its diagnostic performance against IMR were analysed. Results: Six studies directly comparing angio-IMR with IMR were included. Data extraction rate was 85.1% (582/684 vessels). There was a linear correlation between angio-IMR and IMR (β=0.483, R square=0.298) (Figure 1A). Pooled sensitivity was 77%, specificity was 66%, positive predictive value was 65%, negative predictive value was 78%, and accuracy was 71.0%. Pooled area under receiver operator curve of angio-IMR for predicting IMR diagnosed coronary microvascular disease was 0.754 (95% confidential interval 0.715 to 0.793) (Figure 1B). Similar diagnostic performance was observed in subgroups of patients with or without ST-segment elevation myocardial infarction. Conclusions: Currently available angio-IMR showed a clearly useful discrimination and diagnostic performance against the standard of wire based IMR. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): China Scholarship Council